2020
DOI: 10.1515/dx-2020-0111
|View full text |Cite
|
Sign up to set email alerts
|

Updated overview on the interplay between obesity and COVID-19

Abstract: The worldwide spread of coronavirus disease 2019 (COVID-19) has generated a global health crisis and more than a million deaths so far. Epidemiological and clinical characteristics of COVID-19 are increasingly reported, along with its potential relationship with overweight and/or obesity. Therefore, we aim here to review the current scientific literature on the impact of overweight and/or obesity among hospitalized patients who have developed severe or critical forms of COVID-19. Following PRISMA guidelines, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Using the AMSTAR-2 appraisal tool to judge the methodological quality, 25 14,[17][18][19][20][21][24][25][26]28,30,32,33,35,37,[41][42][43][44][45][46][47][48][49][50] of the 37 studies were evaluated as 'Low'or 'Critically low'-quality studies; 15 14,[17][18][19][20][21][24][25][26]28,30,32,33,35,37 and 10, [41][42][43][44][45][46][47][48][49][50] respectively (Table S2). The individual results of the AMSTAR-2 study quality assessment are...…”
Section: Results Of Study Appraisalmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the AMSTAR-2 appraisal tool to judge the methodological quality, 25 14,[17][18][19][20][21][24][25][26]28,30,32,33,35,37,[41][42][43][44][45][46][47][48][49][50] of the 37 studies were evaluated as 'Low'or 'Critically low'-quality studies; 15 14,[17][18][19][20][21][24][25][26]28,30,32,33,35,37 and 10, [41][42][43][44][45][46][47][48][49][50] respectively (Table S2). The individual results of the AMSTAR-2 study quality assessment are...…”
Section: Results Of Study Appraisalmentioning
confidence: 99%
“…Using the AMSTAR‐2 appraisal tool to judge the methodological quality, 25 14,17–21,24–26,28,30,32,33,35,37,41–50 of the 37 studies were evaluated as ‘Low’‐ or ‘Critically low’‐quality studies; 15 14,17–21,24–26,28,30,32,33,35,37 and 10, 41–50 respectively (Table S2). The individual results of the AMSTAR‐2 study quality assessment are shown in Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is the most frequent previous health condition among COVID-19 patients and has a high proportion of deaths to cases. Onorato et al (2020) found four studies regarding the effect of obesity on mortality of COVID-19 patients in the United States and the United Kingdom, all of them concluding that obesity is related to the risk of death.…”
Section: The Effect Of Previous Health Conditionsmentioning
confidence: 99%